Frost flowers on young Arctic sea ice: The climatic, chemical, and microbial significance of an emerging ice type. Issue 20 (23rd October 2014) - Barber, D. G.; Ehn, J. K.; Pućko, M.; Rysgaard, S.; Deming, J. W.; Bowman, J. S.; Papakyriakou, T.; Galley, R. J.; Søgaard, D. H.
Abstract Ongoing changes in Arctic sea ice are increasing the spatial and temporal range of young sea ice types over which frost flowers can occur, yet the significance of frost flowers to ocean‐sea ice‐atmosphere exchange processes remains poorly understood. Frost flowers form when moisture from seawater becomes available to a cold atmosphere and surface winds are low, allowing for supersaturation of the near‐surface boundary layer. Ice grown in a pond cut in young ice at the mouth of Young Sound, NE Greenland, in March 2012, showed that expanding frost flower clusters began forming as soon as the ice formed. The new ice and frost flowers dramatically changed the radiative and thermal environment. The frost flowers were about 5°C colder than the brine surface, with an approximately linear temperature gradient from their base to their upper tips. Salinity and δ18O values indicated that frost flowers primarily originated from the surface brine skim. Ikaite crystals were observed to form within an hour in both frost flowers and the thin pond ice. Average ikaite concentrations were 1013 µmol kg−1 in frost flowers and 1061 µmol kg−1 in the surface slush layer. Chamber flux measurements confirmed an efflux of CO2 at the brine‐wetted sea ice surface, in line with expectations from the brine chemistry. Bacteria concentrations generally increased with salinity in frost flowers and the surface slush layer. Bacterial densities and taxa indicated that a selective process occurred at the ice surface and confirmed the general pattern of primary oceanic origin versus negligible atmospheric deposition.